Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

(6p + 4q)(-2p + 9q) simplify please help me with this

Sagot :

Well first you have to multiply using FOIL, so...
-12p² + 54qp -8qp +36q²
-12p² + 46qp + 36q² is the simplified answer
Hope that helps :)
Lilith
[tex](6p + 4q)(-2p + 9q) =\\ \\=-2p\cdot 6p + 9q\cdot 6p -2p\cdot 4q + 9q\cdot 4q=\\ \\=-12p^{2}+54pq-8pq+36q^2=\\ \\ =-12p^{2}+46pq +36q^2[/tex]